Take a deep breath : clear the air for the health of your child - Shapiro, Nina. (Hackensack, N.J. : World Scientific, 2012)
At some point during childhood, 80 to 90% of all children have a breathing problem. 'Take a Deep Breath' is a comprehensive, accessible, and indispensible guide for parents, caregivers, teachers, and healthcare providers on the subject of children's breathing issues. From the uppermost part of the airway - the nose, to the lowermost part - the lungs, Dr Nina Shapiro explains which problems are truly worrisome, and which are actually normal stages in a child's growth. 'Take a Deep Breath' will enable you to do just that, take a deep breath, and get a better, clearer understanding of what's goin.
Section 1. Newborn to three months -- section 2. Three months to one year -- section 3. One to five years.
Includes bibliographical references and index.
WorldCat record variable field(s) change: 650
Keywords: Pediatric respiratory diseases; Respiratory organs -- Diseases; Infants -- Diseases; Children -- Health and hygiene; Respiratory emergencies; Respiration; Respiratory infections; Asthma; Respiratory allergy; Pediatrics; Children; Respiration; Respiration Disorders; Respiratory Tract Infections; Asthma; Respiratory Hypersensitivity; Pediatrics; Child; Appareil respiratoire -- Maladies, chez l'enfant.; Appareil respiratoire -- Maladies; Nourrissons -- Maladies; Urgences respiratoires; Respiration; Appareil respiratoire -- Infections; Asthme; Allergie respiratoire; Pédiatrie.; Enfants; children (people by age group); HEALTH & FITNESS -- Children's Health; MEDICAL -- Pediatrics; Children -- Health and hygiene; Infants -- Diseases; Pediatric respiratory diseases; Respiratory emergencies; Respiratory organs -- Diseases; Popular Work; Electronic books